2010
DOI: 10.1104/pp.110.153718
|View full text |Cite
|
Sign up to set email alerts
|

CLE Peptides Control Medicago truncatula Nodulation Locally and Systemically      

Abstract: The CLAVATA3/embryo-surrounding region (CLE) peptides control the fine balance between proliferation and differentiation in plant development. We studied the role of CLE peptides during indeterminate nodule development and identified 25 MtCLE peptide genes in the Medicago truncatula genome, of which two genes, MtCLE12 and MtCLE13, had nodulation-related expression patterns that were linked to proliferation and differentiation. MtCLE13 expression was up-regulated early in nodule development. A high-to-low expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
409
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(454 citation statements)
references
References 95 publications
(151 reference statements)
26
409
2
4
Order By: Relevance
“…If NOOT and COCH regulate (or interact with) stem cell activity in the meristem, as suggested by the meristem enlargement observed in the noot and coch mutant nodules, then we can hypothesize that a WUSCHEL-HOMEOBOX/CLE regulatory loop operates in the nodule meristem. In support of this hypothesis, Mortier et al (2010) have shown that at least two CLE peptides are expressed in the meristematic region of the nodule. It will thus be interesting to know if the cytokinininduced Mt-WUSCHEL described by Chen et al (2009) is also expressed in the nodule meristem.…”
Section: Discussionmentioning
confidence: 54%
“…If NOOT and COCH regulate (or interact with) stem cell activity in the meristem, as suggested by the meristem enlargement observed in the noot and coch mutant nodules, then we can hypothesize that a WUSCHEL-HOMEOBOX/CLE regulatory loop operates in the nodule meristem. In support of this hypothesis, Mortier et al (2010) have shown that at least two CLE peptides are expressed in the meristematic region of the nodule. It will thus be interesting to know if the cytokinininduced Mt-WUSCHEL described by Chen et al (2009) is also expressed in the nodule meristem.…”
Section: Discussionmentioning
confidence: 54%
“…Conversely, knockdown of Medicago truncatula MtCLE12 and MtCLE13 resulted in a significant increase in nodule number 17 . Functionally similar CLE genes have also been identified in other leguminous species [18][19][20][21] . Thus, CLE-RS peptides are strong candidates for the root-derived signals that might act as ligands for HAR1.…”
mentioning
confidence: 83%
“…Rhizobial NFs rapidly trigger nuclear calcium oscillations in root hair cells (Lévy et al, 2004;Miwa et al, 2006), which transcriptionally activate key symbiotic (SYM) genes (e.g. NODULE INCEPTION and NODULATION SIGNALING PATHWAY1 and 2 [Kaló et al, 2005;Smit et al, 2005] and MtCLV3/ESR-RELATED12 and 13 [MtCLE12 and 13; Mortier et al, 2010;Saur et al, 2011]). Nodulation is also positively and negatively controlled by complex, context-dependent interactions with various hormones and peptides (Penmetsa and Cook, 1997;Gonzalez-Rizzo et al, 2006;Penmetsa et al, 2008;Mortier et al, 2010;Plet et al, 2011;Saur et al, 2011;Mortier et al, 2012;Larrainzar et al, 2015;van Zeijl et al, 2015).…”
mentioning
confidence: 99%
“…NODULE INCEPTION and NODULATION SIGNALING PATHWAY1 and 2 [Kaló et al, 2005;Smit et al, 2005] and MtCLV3/ESR-RELATED12 and 13 [MtCLE12 and 13; Mortier et al, 2010;Saur et al, 2011]). Nodulation is also positively and negatively controlled by complex, context-dependent interactions with various hormones and peptides (Penmetsa and Cook, 1997;Gonzalez-Rizzo et al, 2006;Penmetsa et al, 2008;Mortier et al, 2010;Plet et al, 2011;Saur et al, 2011;Mortier et al, 2012;Larrainzar et al, 2015;van Zeijl et al, 2015). Collectively, these signals, along with the NF/SYM pathway, determine how, when, and where nodules form, as well as the overall nodule number on the root system (Penmetsa and Cook, 1997;Oldroyd et al, 2011).…”
mentioning
confidence: 99%